Identifikasi Jiwa Kewirausahaan pada Pemilik Elisabeth Max di Semarang - Vonnie Jane Marsellina; Y. Sugiharto (JEMAP, 2018)
The objective of this research is to identify the entrepreneurial spirit of  Elisabeth Max owner based on Meredith’s theory of entrepreneurship. In this research, there were 6 respondents. The sampling technique use is purposive sampling, namely sampling by certain requirements or judgments. In this research, it shoud be studied  quantatively by likert scale. Based on the study, it was conclude that the owner was included as a self confidence person, task and result oriented, risk taker, leader spirit, original, and future oriented.